Dynamic tax revenue buoyancy estimates for a panel of OECD countries - Yota Deli; Abian Garcia Rodriguez; Ilias Kostarakos; Petros Varthalitis (The Economic and Social Research Institute (ESRI), 2018)
In this paper we provide short- and long-run tax buoyancy estimates for a panel of OECD countries. Our results indicate that total tax revenue estimates are not different from unity, corporate income tax buoyancies exceed unity both in the long- and the short-run, while personal income tax buoyancies are smaller than unity; these results are robust to controlling for changes in the respective tax rates. Moreover, after taking into account the fluctuations of the business cycle, we observe that CIT estimates are larger during periods of contraction rather than periods of economic expansion; these results hold both for the whole panel and the Irish economy. Moreover, we examine the effects of using GNP instead of GDP as a base of economic activity for the Irish economy. Although the results are qualitatively the same, the differences need to be taken into account, especially form an economic policy point of view.
Keywords: H24; H25; H27; H30; 330; Tax revenue buoyancy; Dynamic panels; Error correction models